Bleeding Post Constriction Ring Release Surgery Causing Lower Limb Ischemia in an Infant with Undetected Hemophilia B - Sabapathy, S. Raja; Mohan, Monusha; Venkateswaran, G.; Ranjani, Shashi (Indian Journal of Plastic Surgery, 2021)
Bleeding in the immediate postoperative period causing compromised limb circulation is an alarming complication. It is known to occur in coagulation disorders like hemophilia. When such complications happen in a child with no previous history of bleeding problems, one has to have a low threshold for suspecting a coagulation disorder. Repeated diffuse bleeding in the whole of the surgical wound with no specific bleeders must raise the suspicion and appropriate laboratory tests must immediately be ordered. Bleeding in coagulation disorders can stop only with supplementation of the appropriate missing clotting factor. Early diagnosis is important to avoid excess morbidity. We are reporting a 6-month-old child who underwent surgery for constriction ring syndrome in the limbs with Z-plasty and developed impending limb ischemia due to bleeding in the immediate postoperative period. The article emphasizes the need to think of the possibility while encountering recurrent bleeding in the postoperative period.
Keywords: hemophilia; constriction ring syndrome; postoperative bleeding